1985
DOI: 10.1021/la00061a019
|View full text |Cite
|
Sign up to set email alerts
|

Crystal growth of calcium phosphates in the presence of magnesium ions

Abstract: tradiol in 50% v/v methanol/water 0.1 M buffer. However, when the percentage of methanol was reduced to 5% v/v, an adsorptive couple was observed even at "pH" 4.0.Cyclic voltammograms of -estradiol (Figure 16B), the stereoisomer of ß-estradiol in the 17-OH position, under identical conditions to the /3-estradiol experiments, showed significant differences in position and shape of the adsorptive responses relative to that of ß-estradiol (Figure 16A). Oestrone (a phenolic steroid not possessing a 17-OH group) di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
122
0
2

Year Published

1988
1988
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 213 publications
(132 citation statements)
references
References 3 publications
6
122
0
2
Order By: Relevance
“…The mechanism [1, 16,29]. In seeded growth experiments, however, of transformation probably involves the growth of it has been shown that magnesium ions strongly brushite from solution at the expense of the retard the growth of OCP whereas the growth of amorphous phase, rather than a direct solid to brushite is hardly affected [33,34]. Thus, while solid transformation.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism [1, 16,29]. In seeded growth experiments, however, of transformation probably involves the growth of it has been shown that magnesium ions strongly brushite from solution at the expense of the retard the growth of OCP whereas the growth of amorphous phase, rather than a direct solid to brushite is hardly affected [33,34]. Thus, while solid transformation.…”
Section: Discussionmentioning
confidence: 99%
“…In bone, Mg 2ϩ ions bind at the surface of the hydroxyapatite crystals. Mg 2ϩ increases the solubility of P i and Ca 2ϩ hydroxyapatite and thereby acts on the crystal size and formation (443). Mg 2ϩ induces osteoblast proliferation; therefore, Mg 2ϩ deficiency results in decreased bone formation (320) (FIGURE 4) Mg 2ϩ -deficient rats have reduced osteoblast numbers and decreased bone mass (434).…”
Section: B Magnesium In Bonementioning
confidence: 99%
“…Mg 2ϩ increases the solubility of the minerals and thereby acts on the crystal size and formation (443). Crystals in Mg 2ϩ -deficient bone are larger, and the bone may therefore be brittle and more susceptible to fractures (89).…”
Section: H Magnesium In Bonementioning
confidence: 99%
“…Furthermore, the hypothesis of amorphous calcium phosphate occurrence in the first phases of alteration is consistent with high pH and reagent concentration, despite the meta-stability of this compound [17]. Moreover, the presence of Mg in the system from the dissolution of dolostones and magnesium limestones stabilizes the amorphous calcium phosphate and brushite, inhibiting the crystallization of apatite and less extensively of octacalcium phosphate [46]. The transformation of calcium phosphate precursors into apatite was locally inhibited by the acidic pH and the presence of stabilizing ions in solution [47].…”
Section: Discussionmentioning
confidence: 55%